2022
DOI: 10.1177/13670069211058268
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual children acting as language brokers in Italy: Their affective and cognitive attitudes about the practice

Abstract: Aims and objectives: This paper sets out to examine Italian bilingual children’ attitudes about Child Language Brokering (CLB), with a focus on the perceived feelings (affective component of attitudes) and benefits (cognitive component of attitudes) related to CLB. The aim is to study the presence of any relationship between the affective and cognitive components of child language brokers’ attitudes, since they can affect the outcomes of CLB and their analysis can provide tools to reduce the stressors related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Given CLBs' engagement in communicative events, empirical studies have also focused on the communicative roles and brokering strategies adopted by CLBs. The majority of these studies are from the USA (Orellana et al 2003(Orellana et al , 2012Perry 2009Perry , 2014Orellana 2009, 2014;Valdés, Chavez, and Angelelli 2000) and Europe (Ceccoli 2020(Ceccoli , 2022García-Sánchez 2010;Napier 2021;Pugliese 2017;Rossato 2019). The results obtained have highlighted that CLBs were able to successfully convey the main communicative goals of the monolingual participants by using flawed, albeit functional, English (Valdés, Chavez, and Angelelli 2000).…”
Section: Fluidity Of Clbs' Roles: Spotlight On Their Communicative Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Given CLBs' engagement in communicative events, empirical studies have also focused on the communicative roles and brokering strategies adopted by CLBs. The majority of these studies are from the USA (Orellana et al 2003(Orellana et al , 2012Perry 2009Perry , 2014Orellana 2009, 2014;Valdés, Chavez, and Angelelli 2000) and Europe (Ceccoli 2020(Ceccoli , 2022García-Sánchez 2010;Napier 2021;Pugliese 2017;Rossato 2019). The results obtained have highlighted that CLBs were able to successfully convey the main communicative goals of the monolingual participants by using flawed, albeit functional, English (Valdés, Chavez, and Angelelli 2000).…”
Section: Fluidity Of Clbs' Roles: Spotlight On Their Communicative Rolementioning
confidence: 99%
“…CLB is a field of inquiry in its own right. From initial field observations (Harris and Sherwood 1978) to more structured empirical research projects (Valdés, Chavez, and Angelelli 2000;Weisskirch 2017), interest in CLB has been on the rise as evi-dent in the increase in research funding allocated to specific projects (e.g., Arts and Humanities Research Council "Translating Cultures" in the United Kingdom , The National Research Centre on the Gifted and Talented "Identifying, teaching and assessing the gifted through cultural lenses" in the US (1996)(1997)(1998)(1999)(2000), as well as in the conferences devoting strands to CLB (e.g., the bi-annual International Conference on Non-Professional Interpreting and Translation celebrated in Cyprus (2023), Amsterdam (2021), Stellenbosch (2018), Winterthur (2016), Germersheim (2014), andBologna (2012)) and in the number of publications (Angelelli 2010(Angelelli , 2016Antonini et al 2017;Ceccoli 2022;Evrin and Meyer 2016;Napier 2021;Valdés, Chavez, and Angelelli 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown associations between immigrants’ and refugees’ choices of home language policies (i.e., a shift to the majority language of the host country or maintenance of their home language) and language attitudes (Alsahafi, 2022; Gogonas & Maligkoudi, 2022; Makarova et al, 2017). Attitudes in general are “favourable, unfavourable or neutral evaluations of an attitude object that can be represented by a person, a product, or a social group” (Ceccoli, 2022, p. 337). Attitudes may include the “affective component” (feelings or emotions), “the behavioural component” (impact on human behavior), and “the cognitive component” (beliefs) (Ceccoli, 2022, p. 337).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes in general are “favourable, unfavourable or neutral evaluations of an attitude object that can be represented by a person, a product, or a social group” (Ceccoli, 2022, p. 337). Attitudes may include the “affective component” (feelings or emotions), “the behavioural component” (impact on human behavior), and “the cognitive component” (beliefs) (Ceccoli, 2022, p. 337). Language attitudes are seen as parts of “broader ideologies” and are associated with values attributed to languages “in specific sociocultural domains,” as well as a perceived importance of these languages.…”
Section: Introductionmentioning
confidence: 99%
“…Affective Component pertains to the sentiments and emotions exhibited by the consumer in consideration of the object (Ceccoli, 2022). This component can vary in expression ranging from feeling very unhappy to very happy.…”
mentioning
confidence: 99%